2010
DOI: 10.1017/s2040470010000786
|View full text |Cite
|
Sign up to set email alerts
|

Sweet sorghum—a local fodder with great potential

Abstract: Sorghum (Sorghum bicolor L. Moench) is the fifth most important cereal crop in acreage and fourth most important in production in the world and is the dietary staple of more than 500 million people in 100 countries, primarily in the developing world. The grain is mainly used as animal feed in the developed world. Sorghum is mostly grown in the semi-arid tropics of the world under dryland conditions with low and erratic rainfall. Though it can survive on about 300 mm rainfall, it responds favourably to irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Moisture content analysis is used for the determination of proportionality of solid-to-liquid ratio in the pretreatment and hydrolysis method; with increasing moisture content, it affects the product quality. Again, moisture content affects the ability of conversion of disaccharide sugar into monosaccharide sugar, storage stability, processing behavior, and quality and appearance of sugar [ 33 ]. The analysis of total moisture is used to determine other properties such as volatile matter.…”
Section: Discussionmentioning
confidence: 99%
“…Moisture content analysis is used for the determination of proportionality of solid-to-liquid ratio in the pretreatment and hydrolysis method; with increasing moisture content, it affects the product quality. Again, moisture content affects the ability of conversion of disaccharide sugar into monosaccharide sugar, storage stability, processing behavior, and quality and appearance of sugar [ 33 ]. The analysis of total moisture is used to determine other properties such as volatile matter.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of this stage, herbal extracts are added. When the final °Brix of concentrated juice (syrup) was 72° to 76°Brix after cooling, heating was completely stopped as described by Nimbkar et al (2006).…”
Section: Syrup Preparationmentioning
confidence: 99%
“…54-9 sugar cane variety. Nimbkar et al (2006) showed that sorghum syrup produced from 'Madhura' hybrid sweet sorghum cultivar was preferable in colour than cane syrup. Sweet sorghum syrup can be used as a popular food and liquid sweetener in various food products (Elena, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cette option est plus facile à mettre en oeuvre mais sa durabilité est incertaine et ses résultats sont non mesurables en l'absence de contrôles de performances. Des expériences réussies ont été rapportées (amélioration du poids vif à 3 et 6 mois chez des chevreaux du Maharashtra en Inde grâce au croisement avec la race Boer, Nimbkar et al 2000) mais des échecs également (au Kenya, les chèvres East African et les Galla sont tolérantes à l'infection par Trypanosoma congolense tandis que les Saanen et leurs croisements en meurent (Griffin et Allonby 1979)). Chez le poulet, de nombreux programmes d'introduction de coqs améliorateurs n'ont pas été suivis d'effet, par manque d'organisation de la filière donnant lieu à des croisements non contrôlés, mais aussi par la perte de la capacité d'incubation naturelle des poules croisées en conditions villageoises.…”
Section: B) Sélection Et/ou Croisement ?unclassified